CFO Sebagai Akuntan Profesional, Bankir, dan Kualitas Laporan Keuangan - Kurnianto, Sigit; Mareta, Nola Gama (E-Jurnal Akuntansi, 2023)
The research was conducted with the aim of examining the influence of the presence of a Chief Financial Officer with a professional accountant license on the quality of financial reports. Quantitative data was used in this research with a sample of 137 manufacturing companies listed on the Indonesia Stock Exchange for the 2016-2018 period. The results of this research indicate that the presence of a CFO licensed as a professional accountant does not have a significant positive effect on the quality of financial reports. The results of this research also show that the presence of bankers on the board of directors has a significant negative effect on the quality of financial reports as measured by earnings management. Keywords: Bankers; Board of Directors; Chief Financial Officer; Quality of Financial Statements; Earnings Management